Precalculus (6th Edition) Blitzer

Published by Pearson
ISBN 10: 0-13446-914-3
ISBN 13: 978-0-13446-914-0

Chapter P - Section P.4 - Polynomials - Exercise Set - Page 56: 57



Work Step by Step

RECALL: $(a-b)^3=a^3-3a^2b+ 3ab^2-b^3$ Use the formula above with $a=3x$ and $b=4$ to obtain: $=(3x)^3-3(3x)^2(4)+3(3x)(4^2)-4^3 \\=27x^3-12(9x^2)+9x(16)-64 \\=27x^3-108x^2+144x-64$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.